RELATIONSHIP BETWEEN ANTHROPOMETRIC PARAMETERS AND INTELLIGENCE IN PRESCHOOL CHILDREN FROM RURAL KONKAN - Patil, Suvarna Netaji; Joglekar, chartudatta; Sonavane, Swati; Chavan, Rupali; Bhat, Pallavi; Mohite, Rachana; Deorukhakar, Pralobhana; Jadhav, Dnyaneshwar; Dervankar, Omkar Anant (International Journal of Clinical and Biomedical Research, 2020)
Aim: To study association between anthropometric parameters and intelligence in preschool children from Rural KONKAN. Method: Children between 3 to7 years of age were examined for anthropometry, dietary recall and Intelligence (Intelligent Quotient-IQ) assessment from rural anganwadis. IQ test was performed by clinical psychologist using Binet-Kamat test of intelligence (version 4). Nutritional information was collected from 24- hour dietary recall and food diversity. Results: Results were interpreted using Prorated IQ We studied 159 (82 boys, 78 girls) out of which 15 (9.6%) had higher IQ. 25 (15.8%) were born LBW. Anthropometry classification showed that 61 (38.4%) were stunted and 25(15.7%) were wasted. According to IOTF, 72 (46%) were thin, 83(52%) were normal and 3 (2%) were overweight. we found that there is no significant difference in IQ with respect to anthropometric parameters, birth weight and nutritional status. Conclusion: We could not find any association of anthropometric parameters with IQ inspite of high prevalence of malnutrition. Brain is vital organ which can be protected by redistribution of blood flow at the cost of other organs like liver and abdominal viscera, which are the markers for future risk of diabetes. There is need to improve nutritional status. New update of IQ test is much needed as the current test is more than 50 years old and does not take into account the social, cultural transition over last 2 decades.